Improved deadbeat FC-MPC based on the discrete space vector modulation method with efficient computation for a grid-connected three-level inverter system - Alsofyani, Ibrahim Mohd; Lee, Kyo Beum (Energies, 2019)
The utilization of three-level T-type (3L T-type) inverters in finite set-model predictive control (FS-MPC) of grid-connected systems yielded good performance in terms of current ripples and total harmonic distortions. To further improve the system’s performance, discrete space vector modulation (DSVM) was utilized to synthesize a higher number of virtual voltage vectors. A deadbeat control (DBC) method was used to alleviate the computational burden and provide the optimum voltage vector selection. However, 3L inverters are known to suffer from voltage deviation, owing to the imbalance of the neutral-point voltage. We have proposed a simplified control strategy for balancing the neutral point in the FS-MPC with DSVM and DBC of grid-connected systems, not requiring a weighting factor or additional cost function calculation. The effectiveness of the proposed method was validated using simulation and experiment results. Our experimental results show that the execution time of the proposed algorithm was significantly reduced, while its current quality performance was not affected.
Keywords: Computation efficiency; Deadbeat control; Discrete space vector modulation; Grid connected systems; T-type inverter; Three level systems; Computation efficiency; Deadbeat control; Discrete space vector modulation; Grid connected system; Model predictive control; T-type inverter; Three-level system